Is calorie restriction with sodium-glucose cotransporter 2 inhibitor dapagliflozin a better option for type 2 diabetes mellitus management? - Ruby Dhar; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences)
In a recent multicentric, double-blinded, randomized, placebo-controlled trial by Liu et al., involving 328 subjects aged 20–70 years with type 2 diabetes for ~ 6 years and with body mass index >25, dapagliflozin (10 mg/day or placebo) with calorie restriction resulted in a significantly higher rate of remission of diabetes compared with calorie restriction alone. The main objectives evaluated are diabetes remission (characterized as glycated hemoglobin <6.5% and fasting plasma glucose <126 mg/dL without the use of any antidiabetic medications for a minimum of 2 months) while the secondary objectives are variations in body weight, waist size, body fat percentage, blood pressure, glucose levels, and serum lipid levels after 12 months. Dapagliflozin, sold under the brand names Farxiga (US) and Forxiga (EU), is a hypoglycemia medication used to treat type 2 diabetes. Developed by Bristol-Myers Squibb in partnership with AstraZeneca, it is on the World Health Organization’s List of Essential Medicines for diabetes management.